2014
DOI: 10.1016/j.rbmo.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre study of the clinical relevance of screening IVF patients for carrier status of the annexin A5 M2 haplotype

Abstract: Thrombophilia and impaired placental vasculature are a major cause of adverse pregnancy outcome. In 2007, a new hereditary factor for obstetric complications and recurrent pregnancy loss (RPL) was identified as a sequence variation in the core promoter of the annexin A5 gene, ANXA5, called the M2 haplotype. M2 carriership has been demonstrated in couples with recurrent miscarriage and its origin is embryonic rather than specifically maternal, confirmed by subsequent papers. The M2 haplotype is the first report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…On the other hand, uncertainties in the exact timing of conception allow for ±1 to 2 weeks difference, when recording the timing of pregnancy loss. Alternatively, M2/ ANXA5 might not only have a role in placental vascular remodelling but also in the process of embryonic implantation, as recently suggested (Fishel et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, uncertainties in the exact timing of conception allow for ±1 to 2 weeks difference, when recording the timing of pregnancy loss. Alternatively, M2/ ANXA5 might not only have a role in placental vascular remodelling but also in the process of embryonic implantation, as recently suggested (Fishel et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…Pituitary suppression for ovarian stimulation and oocyte maturation has been described previously (Fishel et al, 2014).…”
Section: Ovarian Stimulation Protocolsmentioning
confidence: 99%
“…Matsubayashi et al demonstrated that RIF patients produce anti-ANXA5 significantly more often than controls (8.3% vs. 1.1%, p < 0.05) and consequently postulate anti-ANXA5 antibodies as risk factor for RIF [40]. Currently, there is only one multicenter study by Fishel et al analyzing the M2/ANXA5 haplotype in infertility couples undergoing ART procedure [41]. They reported a M2 carrier status of 44% in IVF couples (n = 157; one or both partners), 24% of females, 26% of males, and 37% of couples with unexplained infertility [41].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is only one multicenter study by Fishel et al analyzing the M2/ANXA5 haplotype in infertility couples undergoing ART procedure [41]. They reported a M2 carrier status of 44% in IVF couples (n = 157; one or both partners), 24% of females, 26% of males, and 37% of couples with unexplained infertility [41]. In spite of these intruiging results, the relevance of M2/ANXA5 for RIF has not yet been studied.…”
Section: Introductionmentioning
confidence: 99%